Introduction of Food And Drink Using Butterfly Pea Flowers with The PKK Group of Karangmojo Ploso Village Jombang - Nur 'Azah; Abdullah Aminuddin Aziz; Moh. Syamsul Falah; Lukman Hakim; Muhammad Al-Fatih (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The butterfly pea flower is becoming and increasingly popular in Indonesia as a flower that has a positive impact can use for combine with food and drink and also for medicine. The aim of this dedication is to describe the introduction of food and drinks using butterfly pea flowers and explain the inhibiting and supporting factors during the process of introducing food and drinks using butterfly pea flowers. The dedication used a qualitative approach. The dedication was carried out in Karangmojo Village, Ploso, Jombang, there were 35 participants. Data collection uses direct interviews, observation and documentation. Data analysis uses triangulation. The results of the dedication showed that the implementation of the introduction of food and drinks using butterfly pea flowers given to the PKK group in Karangmojo Village, Ploso, Jombang went well. The material presented was related to the understanding of butterfly pea flowers, their components, benefits, opportunities for the business sector in cultivating butterfly pea flowers and demonstrations of food and butterfly pea flowers. The inhibiting factor is that human resources are still minimal in using the butterfly pea flower and there is no quality management of food and beverage production using the butterfly pea flower. The supporting factors are high curiosity and a willingness to learn more about the butterfly pea flower. Conclusion: The introduction of food and drinks using butterfly pea flowers with the PKK group in Karangmojo Ploso Jombang Village was carried out well. The material was delivered to participants without any problems. Solutions have been found for the inhibiting factors along with supporting factors.